Gemeentebou in Suid-Afrikaans-Nederlandse perspektief: Praktiese teologie, diakoniologie of ekklesiologie? - L M Erasmus (Acta Theologica)
Congregation building is a theological discipline in the field of Practical Theology. The discipline is handled according to the communicative theological operational science paradigm. A survey of the literature confirms undoubtedly that deep-rooted differences exist with regards to the encyclopaedic placement of the discipline. As a sub-discipline of Practical Theology, congregation building is typical of a new science paradigm. This new approach thus affects the reformed ecclesiological viewpoint in the light of Scripture and the reformed confession in a negative way. The break between reformed and confessional premises on the one hand and a scientific theological approach complemented with insights and methods of the social sciences on the other hand, testifies of a paradigm shift in the operational science approach. Therefore, a new encyclopeadic approach for congregation building regarding Ecclesiology is considered. A Scriptural church order - as the means by which the reign of Christ and the building up of the congregation can emerge, hanging together without tension - is considered from a reformed and diaconiological perspective. The subject is dealt with in the light of a Netherland-South-African perspective because of the similarities in the theological views and the criticism on congregation nbuilding in the two countries.